CALCULATION OF THE NUMBER AND CAPACITY OF TRANSFORMERS THROUGH THE LOAD FACTOR - Qurbonova, Barno; Qurbonov, Abror (Физико-технологического образование, 2024)
This article analyzes the number and capacity of transformers to be installed in order to reduce power losses and improve efficiency in the event of a plant's need for electricity